2010
DOI: 10.1111/j.1365-2850.2010.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of staff attitudes and responses to people with dementia who are aggressive in residential care settings

Abstract: Aggression is reportedly common among older people with dementia in residential care. The attitudes of staff in care homes and strategies they use are under researched. Theoretical models that may be used to both understand and respond to such behaviour exist. They are the standard and person-centred paradigms. The aim of this study was to explore the views of nursing staff about aggressive behaviour in people with dementia and strategies used in practice. A survey of the attitudes of staff in six dementia car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 19 publications
4
62
0
1
Order By: Relevance
“…Aggression may be attributable to psychosocial-environmental factors or the complex interaction of patients, staff and inpatient unit culture influences [8]. It may be due to the inability of elderly patients with dementia to communicate their needs effectively [9], poor staff-to-patient interactions or the environment of care [9,10], overcrowding, lack of privacy, lack of activities, weak clinical leadership [11], being denied something [7], and restricting patients’ freedom [12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggression may be attributable to psychosocial-environmental factors or the complex interaction of patients, staff and inpatient unit culture influences [8]. It may be due to the inability of elderly patients with dementia to communicate their needs effectively [9], poor staff-to-patient interactions or the environment of care [9,10], overcrowding, lack of privacy, lack of activities, weak clinical leadership [11], being denied something [7], and restricting patients’ freedom [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Research into the use of restraint in elderly people has been conducted in general hospitals [28] and nursing home settings [9,10,29]. However, there has been little investigation of the use of these containment practices with elderly persons in old age psychiatry inpatient settings, and the rate and type of restraint use can vary, even within neighbouring units [30].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsford et al (2011), in a United Kingdom survey of staff attitudes toward older aggressive people with dementia in residential care settings, reported that aggressive behaviour was viewed more so as an interpersonal phenomenon attributable to situational events (e.g., unfavourable interactions with others or the environment of care), and staff responses to this behaviour were predominantly informed by a person-centred approach (e.g., deescalation) than containment methods (e.g., medication, restraint, and seclusion). However, a survey of aggression in a high secure hospital in the United Kingdom, by Pulsford et al (2013) reported that staff held mixed attitudes about the causes and management of patient aggression.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Aggression may be due to psychosocial-environmental influences; the interaction of patients, relatives, and staff; the culture of the inpatient setting; or some combination of these (Hamrin, Iennaco, & Olsen, 2009 The first system is the microsystem, which incorporates the patient's interactions in the immediate setting (e.g., restricting patients' freedom in the inpatient unit (Papadopoulos et al, 2012) with other people (e.g., incapacity of elderly patients with dementia to communicate effectively (Duxbury, Pulsford, Hadi, & Sykes, 2013) and inadequate staff-topatient communication Pulsford et al, 2011), and with symbols and language (the semiotic system). Influences at this level include, for instance, service user characteristics (e.g., sociodemographic, psychological, personality and biological factors, symptomatology, and cognitive functioning) and his or her interactions with other patients, clinicians, and relatives.…”
Section: Ecological Theory Of the Causes Of Aggressionmentioning
confidence: 99%
“…Trotzdem ist es für Pflegepersonen unüblich, Aggressionen zu thematisieren. Zudem zeigt die Literatur, dass noch wenig über aggressives Verhalten von Menschen mit Demenz bekannt ist und für Pflegepersonen eher wenig Präventions-und Interventionsprogramme im Umgang mit aggressivem Verhalten angeboten werden (Hahn & Metzenthin, 2010;Pulsford & Duxbury, 2006;Skovdahl, Kihlgren & Kihlgren, 2003;Zeller, Hahn, Needham, Kok, Dussen & Halfens, 2009 (Becker & Hahn, 2011;Duxbury, 2002;Franz, Zeh, Schablon, Kuhnert & Nienhaus, 2010;Pulsford, Duxbury & Hadi, 2010).…”
Section: Introductionunclassified